Edukasi Kesehatan “Kenali Tanda Dan Gejala Stroke Melalui Metode FAST” Di Kampung Grogol Kota Depok - Dea Rosaline, Mareta; Diah Tika Anggraeni; Lumban Tobing , Duma; Florensia, Lima; Deswita Chandra, Winur; Sekar Lili Yuananda (Jurnal Pengabdian Masyarakat Bakti Parahita, 2024)
A stroke is a damage to brain tissue because the blood supply cessation or reduction suddenly. In the working area of ​​the Limo Health Center, Grogol Village, Depok City, the area for non-communicable diseases is quite high, such as stroke, diabetes mellitus, and hypertension. Knowledge and the ability to detect stroke early in the community are needed To prevent stroke in this community group. The aims to increase knowledge and ability to detect stroke early in the adult and elderly age group in Grogol Village, Depok City. The team in this community service are students and lecturers of the Undergraduate Nursing Program at UPN Veteran Jakarta with community partners and 28 Grogol Village Health Cadres in Grogol Village, Depok City. Methods providing education on stroke disease, demonstration of stroke prevention exercises, and early detection of FAST then continued with blood pressure and cholesterol checks. Results of the service activity intervention showed that there was an increase in knowledge and an increase in the skills of cadres and the community after being given counseling. The results of the pre-post test in the community showed that there was an increase in public knowledge about stroke in as many as 26 people (92.8%). The results achieved are that some of the participants have been able to do early detection of stroke with FAST. The recommendation made is that it is hoped that the community will get a continuous process of assistance during monitoring and evaluation in carrying out early detection, prevention, and first aid in stroke.